2006
DOI: 10.1111/j.1365-294x.2006.03064.x
|View full text |Cite
|
Sign up to set email alerts
|

A chloroplast genealogy of myrmecophyticMacarangaspecies (Euphorbiaceae) in Southeast Asia reveals hybridization, vicariance and long‐distance dispersals

Abstract: Macaranga (Euphorbiaceae) includes about 280 species with a palaeotropic distribution. The genus not only comprises some of the most prominent pioneer tree species in Southeast Asian lowland dipterocarp forests, it also exhibits a substantial radiation of ant-plants (myrmecophytes). Obligate ant-plant mutualisms are formed by about 30 Macaranga species and 13 ant species of the genera Crematogaster or Camponotus. To improve our understanding of the co-evolution of the ants and their host plants, we aim at reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 57 publications
(93 reference statements)
4
86
0
Order By: Relevance
“…As our data are from a maternally inherited organelle genome (the chloroplast), an argument can be made that the lack of correlation between morphotypes and genotypes is due to hybridization and chloroplast capture (resulting in reticulate inheritance of the chloroplast genome). Several studies have found evidence for extensive chloroplast capture (Steane et al 1998;Palme et al 2004;Bänfer et al 2006;Jakob & Blattner 2006) that in some cases explains the apparent non-monophyly of morphotypes. A study of New Zealand Metrosideros found that chloroplast capture within climatic refugia could entirely explain apparent non-monophyly of those species (Gardner et al 2004).…”
Section: Results (A) Phylogenetic and Comparative Analysesmentioning
confidence: 99%
“…As our data are from a maternally inherited organelle genome (the chloroplast), an argument can be made that the lack of correlation between morphotypes and genotypes is due to hybridization and chloroplast capture (resulting in reticulate inheritance of the chloroplast genome). Several studies have found evidence for extensive chloroplast capture (Steane et al 1998;Palme et al 2004;Bänfer et al 2006;Jakob & Blattner 2006) that in some cases explains the apparent non-monophyly of morphotypes. A study of New Zealand Metrosideros found that chloroplast capture within climatic refugia could entirely explain apparent non-monophyly of those species (Gardner et al 2004).…”
Section: Results (A) Phylogenetic and Comparative Analysesmentioning
confidence: 99%
“…but also proved useful to illustrate haplotype relationships at higher taxonomic levels (Bänfer et al, 2006;Jakob and Blattner, 2006;Kiefer et al, 2009;Gurushidze et al, 2010). Here a clear split is visible in nuclear and chloroplast data, separating a clade of taxa occurring in the west and northeast of the distribution area from the clade of Turkish taxa.…”
Section: Danubensis C Micranthus C Reticulatus C Variegatusmentioning
confidence: 99%
“…In addition to these nuclear loci, we also analyzed sequences of 3 chloroplast regions. One of these (trnL-F) is often used in plant phylogeography, as it is normally quite variable (e.g., Bänfer et al 2006;Jakob and Blattner, 2006). PCR primers for the other 2 regions (rps16-trnQ and matK-trnK) were newly designed for this study.…”
Section: Introductionmentioning
confidence: 99%
“…From work on lowland taxa and preliminary studies of montane populations (Moyle et al 2005, Moyle et (Sheldon et al 2009, Irham et al 2012. Substantial evidence indicates that lowland bird populations were subdivided, presumably during one or more glacial periods, into forest refugia in western Sundaland and eastern Borneo, as were other groups of Sundaic organisms (e.g., Brandon-Jones 1998, Thomas 2000, Gathorne-Hardy et al 2002, Gorog et al 2004, Bänfer et al 2006, Iwanaga et al 2012, Ohtani et al 2013). This subdivision would have occurred as lowland forest retreated or shifted position and montane forest expanded and dominated central Borneo ( Figure 2B).…”
Section: Black-eye Phylogeography and Bornean Bird Diversificationmentioning
confidence: 99%